Fitting soil extracellular enzyme activity into the complex network of abiotic and biotic soil properties often associated with soil health - Taggart, Megan G.; Baah, Douglas S.; Allen, Sophie; Khan, Zahoor; Arnscheidt, Joerg; Jordan, Phil; O’Hagan, Barry M. G.; Ibrahim, Aliyu D.; Rao, J. R.; Ternan, Nigel G. (Frontiers in Microbiology, 2025)
In this mini review we examine how soil extracellular enzymes play a key role in nutrient cycling, but stress that their activity alone does not fully represent ecosystem processes. We emphasize the need for more contextual environmental data—such as pH, temperature, moisture and nutrient availability—for accurate interpretation of the significance of enzyme activity in carbon and nutrient (N, P) cycling in soil ecosystems. The importance of enzymes within the soil microbiome determines its inherent capacity to support crop growth and often reflects soil quality and soil health, which are in turn governed by multiple different soil properties. Soil enzymes (e.g., phosphatase, glucosidases, glycosaminidases) activity have been used as key soil health bio indicators for monitoring soil nutrient transformations in overgeneralized statements. Although soil enzymes constitute important attributes that are closely linked to the dynamics of soil nutrient transformation and make nutrients available to plants, we suggest a multi-factor assessment for soil health measurement. We propose that this can give a pulse reading of soil nutrient health at crucial times of soil, land use, and crop management practices but that care is required to incorporate temporal soil and land use properties for correct interpretation.